2010
DOI: 10.1093/humrep/deq241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dienogest administration on angiogenesis and hemodynamics in a rat endometrial autograft model

Abstract: DNG inhibited angiogenesis of the ectopic endometrium, with confirmed structural changes in the microvessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 33 publications
1
29
0
2
Order By: Relevance
“…by increasing the NK activity of peritoneal fluid cells and splenic cells. Moreover, Katayama et al 14) have reported the efficacy of dienogest on angiogenesis and hemodynamics in a rat endometrial autograft model that mechanically isolated endometrial fragments transplanted into dorsal skinfold chambers. Katsuki et al 6) used proestrous rats and model of autotransplantation of endometrial tissue to a renal subcapsular site, but in the present study no efficacy of dienogest was observed in the diestrus rats, although most of rat decreased as to volume of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…by increasing the NK activity of peritoneal fluid cells and splenic cells. Moreover, Katayama et al 14) have reported the efficacy of dienogest on angiogenesis and hemodynamics in a rat endometrial autograft model that mechanically isolated endometrial fragments transplanted into dorsal skinfold chambers. Katsuki et al 6) used proestrous rats and model of autotransplantation of endometrial tissue to a renal subcapsular site, but in the present study no efficacy of dienogest was observed in the diestrus rats, although most of rat decreased as to volume of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…We used a rat model in which the endometrium was implanted on the left abdominal wall, and dienogest was administered twice a day starting 1 week after implantation. Katayama et al 14) administered dienogest once a day from day 0 or 4 after implantation, and Katsuki et al 6) once a day from 2 weeks after implantation. The experimental models and administration protocols were different among these three experiments, although the dosages used were almost equal.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the evaluation of gene ablation on eutopic and ectopic endometrial cell growth has been revealing, the studies of pharmacological modulation contrast these observations to a certain extent as both progestogens and PRAs reduce ectopic endometrial cell proliferation and disease burden in pre-clinical rodent models of endometriosis (Bruner-Tran et al, 2006;Chwalisz et al, 1998;Katayama et al, 2010;Katsuki et al, 1998;Stoeckemann et al, 1995). An explanation of this phenomenon compared with the phenotype of PRKO animals has been revealed by studies with PRAs in the non-human primate.…”
Section: Rodentmentioning
confidence: 99%
“…Как ΠΏΡ€ΠΎΠΈΠ·Π²ΠΎΠ΄Π½ΠΎΠ΅ 19-нортСстостСрона ΠΎΠ½ Ρ…Π°Ρ€Π°ΠΊΡ‚Π΅-ризуСтся высокой ΡΠ΅Π»Π΅ΠΊΡ‚ΠΈΠ²Π½ΠΎΡΡ‚ΡŒΡŽ ΠΊ прогСстСроно-Π²Ρ‹ΠΌ Ρ€Π΅Ρ†Π΅ΠΏΡ‚ΠΎΡ€Π°ΠΌ, ΠΌΠΎΡ‰Π½Ρ‹ΠΌ прогСстагСнным Π²ΠΎΠ·Π΄Π΅ΠΉ-ствиСм Π½Π° эндомСтрий, благодаря Ρ‡Π΅ΠΌΡƒ, Π² ΠΎΡ‚Π»ΠΈΡ‡ΠΈΠ΅ ΠΎΡ‚ Π΄Ρ€ΡƒΠ³ΠΈΡ… гСстагСнов, ΠΎΠ±Π»Π°Π΄Π°Π΅Ρ‚ спСцифичСским Π°Π½Ρ‚ΠΈ-ΠΏΡ€ΠΎΠ»ΠΈΡ„Π΅Ρ€Π°Ρ‚ΠΈΠ²Π½Ρ‹ΠΌ, Π°Π½Ρ‚ΠΈΠ°Π½Π³ΠΈΠΎΠ³Π΅Π½Π½Ρ‹ΠΌ, ΠΏΡ€ΠΎΠ°ΠΏΠΎΠΏΡ‚ΠΈ-чСским ΠΈ ΠΏΡ€ΠΎΡ‚ΠΈΠ²ΠΎΠ²ΠΎΡΠΏΠ°Π»ΠΈΡ‚Π΅Π»ΡŒΠ½Ρ‹ΠΌ свойствами ΠΈ Π²ΠΎΠ·-дСйствуСт Π½Π° всС звСнья ΠΏΠ°Ρ‚ΠΎΠ³Π΅Π½Π΅Π·Π° эндомСтриоза [48][49][50][51].…”
unclassified